The distribution of the gender wage gap in Austria: evidence from matched employer-employee data and tax records - René Böheim; Klemens Himpele; Helmut Mahringer; Christine Zulehner (Journal for Labour Market Research, 2013)
We examine the gender wage gap in Austria using new matched employer-employee data from 2007. We estimate quantile regressions and investigate the gender wage gap at the conditional wage distribution of men and women. We decompose the gender wage gap into the parts which are due to different characteristics and different returns to these characteristics. About 60 % of the gender wage gap cannot be explained by differences in human capital or other observable indicators of productivity. Taking differences in the characteristics into account, we find that women earn on average about 11 % less than men. We further estimate that differences in the returns for women and men increase over the wage distribution.
Keywords: J31; J71; 330; Lohnunterschied; geschlechtsspezifische Faktoren; erwerbstätige Frauen; erwerbstätige Männer; Lohnstruktur; Lohndiskriminierung; Lohnhöhe; Österreich